THE UTILIZATION OF LEARNING MULTIMEDIA AS STRATEGIES TO INCREASE STUDENTS LEARNING ACHIEVEMENT (PEMANFAATAN MULTIMEDIA PEMBELAJARAN SEBAGAI STRATEGI PENINGKATAN PRESTASI BELAJAR SISWA) - Perdana, Novrian Satria (EDUTECH, 2016)
Abstract.This study aims to determine the most effective type of learning tool to improve stu-dents’ achievemen . This study uses quasi-experimental method, which connects the causality be-tween variables which are deliberately determined with another variable, with pretest - posttest control group design. The sample of this study is 376 students majoring in accounting at a state vocational school in Jakarta. The results showed: ( 1 ) The use of learning multimedia in the learning process of accounting subject was more effective to improve students’ cognitive abilities in accounting than the use textbooks; ( 2 ) Accounting learning with multimedia was better than learning with text books.Keywords : Learning Media , Multimedia , Learning Achievement .Abstrak.Penelitian ini bertujuan untuk mengetahui jenis sarana pembelajaran apakah yang paling efektif untuk meningkatkan prestasi belajar siswa. Penelitian ini menggunakan metode kuasi eksperimen, yang menghubungkan sebab akibat antara variabel y ang sengaja ditentukan dengan variabel lain, dengan desain pretest-posttest control group design. Sampel dalam penelitian sebanyak 376 siswa SMK Negeri jurusan akuntansi di DKI Jakarta. Hasil penelitian menunjukkan: (1) Penggunaan media pembelajaran multimedia dalam proses pembelajaran akuntansi lebih effektif dalam meningkatkan kemampuan kognitif akuntansi yang dimiliki siswa daripada penggunaan media buku teks. (2) Pembelajaran akuntansi dengan multimedia lebih baik dibandingkan dengan buku teks.Kata Kunci : Media Pembelajaran, Multimedia, Prestasi Belajar.